Eksistensi Aturan Pemidanaan Tidak Pidana Internasional pada Konflik Ukraina dan Jalur Gaza - Dewic Sri Ratnaning; Danang Alvianto (HUMANIORUM, 2026)
This study critically analyzes the existence of international criminal sanctions in the Ukraine and Gaza Strip conflicts from 2023 to 2025. Using a normative legal approach, this study examines the existence of international criminal sanctions, particularly those stipulated in Principle I (individual criminal responsibility), Principle III (denial of official immunity), and Principle IV (denial of superior orders), codified in Articles 25, 27, and 28 of the Rome Statute. Several obstacles to enforcing criminal sanctions are often hampered by the principle of complementarity (Article 17) and the UN Security Council veto mechanism (Article 27(3) of the UN Charter), making the existence of criminal sanctions through ICC decisions unenforceable. This is evident in the failure to execute the arrest warrant against Putin (March 17, 2023) for the deportation of 19,144 Ukrainian children and four simultaneous warrants against Netanyahu, Gallant, and Hamas leaders (May 20, 2024). Six Russian vetoes against Ukraine (2022 2024) and 46 US vetoes related to Israel Palestine since 1972 paralyze the reference to Article 13(b) then to what extent the existence of criminal rules for crimes imposed on the Ukraine and Gaza Strip conflicts in the period 2023-2025, how can the UN council veto rules affect this existence? So it can be concluded that to what extent the criminal rules in punishing perpetrators of international crimes exist so that they can realize an international criminal system that is not only decorative but can also be implemented effectively as a form of deterrence for perpetrators and a last resort in eliminating the existence of international crimes.